2020
DOI: 10.1101/2020.05.05.079608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the replication of SARS-CoV-2 in human cells by the FDA-approved drug chlorpromazine

Abstract: Urgent action is needed to fight the ongoing COVID-19 pandemic by reducing the number of infected people along with the infection contagiousness and severity. Chlorpromazine (CPZ), the prototype of typical antipsychotics from the phenothiazine group, is known to inhibit clathrin-mediated endocytosis and acts as an antiviral, in particular against SARS-CoV-1 and MERS-CoV. In this study, we describe the in vitro testing of CPZ against a SARS-CoV-2 isolate in monkey and human cells. We evidenced an antiviral acti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Terfenadine was withdrawn from the market in 1997 after 12 years due to evidence for cardiac toxicity via the binding to the hERG channel yet may still provide short term benefit as a SARS-CoV-2 prophylactic or acute treatment (Roy et al, 1996). Chlorpromazine was shown to block Epstein-Barr virus (Nemerow and Cooper, 1984) and influenza A virus (Krizanova et al, 1982) and very recently was found to be effective against SARS-CoV-2 in multiple in-vitro assays (Plaze et al, 2020), although we ruled it out early due to cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Terfenadine was withdrawn from the market in 1997 after 12 years due to evidence for cardiac toxicity via the binding to the hERG channel yet may still provide short term benefit as a SARS-CoV-2 prophylactic or acute treatment (Roy et al, 1996). Chlorpromazine was shown to block Epstein-Barr virus (Nemerow and Cooper, 1984) and influenza A virus (Krizanova et al, 1982) and very recently was found to be effective against SARS-CoV-2 in multiple in-vitro assays (Plaze et al, 2020), although we ruled it out early due to cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, CPZ as an anti-COVID-19 candidate is a fair illustration for repositioning the molecule as a treatment for COVID-19 with the findings of the two studies demonstrating in vitro activity against SARS-CoV-2 (Plaze et al, 2020b;Weston et al, 2020). These two pre-print studies demonstrate the in vitro activity of chlorpromazine against SARS-CoV-2 are crucial for proposing a repositioning.…”
Section: Chlorpromazine and Viral Infectionsmentioning
confidence: 84%
“…They are not only repositioning themselves, but also offer repositioning of medication that they know very well. This is the case with the first known antipsychotic medication, CPZ (Plaze et al, 2020a;Plaze et al, 2020b;Stip, 2002;Stip, 2020). In 2020, a Canadian research letter (Stip, 2020) proposed the possibility that CPZ, a medication used in psychiatry for a long time, could potentially be used to counter COVID-19 (Nobile et al, 2020).…”
Section: Chlorpromazine and Coronavirusmentioning
confidence: 99%
See 2 more Smart Citations